The objective of this research is to develop a model of water table fluctuation on tidal lowland area of B/C type. Modeling of water table is expected to support the agriculture development on tidal lowland area, especially on water management due to the important role of water management in the agriculture on tidal lowland area. The water table controls on the particular depth can support the farming system and avoid pyrite oxidation. The model of water table fluctuation which is developed in - Ngudiantoro .; Hidayat Pawitan; M. Yanuar J. Purwanto; Robiyanto H. Susanto (Forum Pasca Sarjana, 2010)
The objective of this research is to develop a model of water table fluctuation on tidal lowland area of B/C type. Modeling of water table is expected to support the agriculture development on tidal lowland area, especially on water management due to the important role of water management in the agriculture on tidal lowland area. The water table controls on the particular depth can support the farming system and avoid pyrite oxidation. The model of water table fluctuation which is developed in this research based on the ellipse concept. The developed model has been tested on the tidal lowland areas in P6-3N Delta Telang I, Banyuasin District, South Sumatra Province. The simulated model showed the promoting result in estimating the depth of water table on tidal lowland area of B/C type. The developed model could explain the proportion of water table depth variation between 89.5% up to 94.7% with standard error estimation varied from 0.029 to 0.042 meters. The model has high sensitivity to the parameter of the water level in the tertiary canals. Key words: modeling, water table, water management, tidal lowland area of B/C type